2012
DOI: 10.1148/radiol.12120051
|View full text |Cite
|
Sign up to set email alerts
|

Repaired Tetralogy of Fallot: Ratio of Right Ventricular Volume to Left Ventricular Volume as a Marker of Right Ventricular Dilatation

Abstract: The RV/LV ratio is more accurate than the RVEDVi in differentiation of significant from insignificant PR. After TOF repair, female and male patients have similar RV/LV ratios despite significant differences in RVEDVi between the sexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 51 publications
6
21
0
1
Order By: Relevance
“…8 The presence of the RV outflow tract (RVOT) aneurysm or akinesia was assessed as described previously. 2 Data on inter-and intraobserver variability of the measurements of ventricular volumes and PR were published previously 10,12 and were comparable to those from other centers.…”
supporting
confidence: 55%
See 2 more Smart Citations
“…8 The presence of the RV outflow tract (RVOT) aneurysm or akinesia was assessed as described previously. 2 Data on inter-and intraobserver variability of the measurements of ventricular volumes and PR were published previously 10,12 and were comparable to those from other centers.…”
supporting
confidence: 55%
“…Selected data on patients with repaired TOF undergoing CMR imaging study in our center were published previously. [9][10][11][12] In particular, we previously analyzed factors associated with biventricular dysfunction in the same study population (31 patients with biventricular dysfunction and 65 patients with normal biventricular systolic functions were selected out of a group of 146 patient; unpublished data).…”
Section: Patients and Methods Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Standard RV Performance and Pulmonary Vascular Resistance We used RV stroke volume (RVSV) as a geometry-independent indicator of RV performance. RVSV was determined as the longed myocarditis due to Kawasaki disease.…”
Section: Rv/lv Diameter Ratiomentioning
confidence: 99%
“…As for the r-TOF group, the RV/LV EDVI ratio (1.55±0.56) in the present study was similar to those in previous reports. 22 Zhang et al reported that the correlations between 3-D echocardiography and cMRI measurements were acceptable. 23 In our next step, we will compare RV volume obtained on 3D-TTE with that on cMRI to validate the accuracy and reproducibility.…”
Section: -21mentioning
confidence: 99%